How do you solve 5( u + 6) = - 3( 3u - 6) + 4u?

2 Answers
Mar 9, 2018

Distribute and then move u over to one side to get

u=-1.2

Explanation:

5(u+6)=-3(3u-6)+4u

5u+30=-9u+18+4u

5u+30=-5u+18

10u+30=18

10u=-12

u=-1.2

Mar 10, 2018

u=(-6)/5

Explanation:

5(u+6)=-3(3u-6)+4u

Distribute

(5)(u)+(5)(6)=(-3)(3u)+(-3)(-6)+4u

5u +30=color(green)(-9u)+18color(green)(+4u)

5u + 30 = -5u + 18

Subtract color(red)(30) from both sides

5u cancel(+30) cancelcolor(red)(-30) = -5u + 18 - 30

5u = -5u -12

Add 5u on both sides

5u + 5u = -5u + 5u - 12

10u = -12

u=(-12)/10

u=(-6)/5